2020
DOI: 10.1016/j.renene.2019.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cool roof and night ventilation in office buildings: A case study in Xiamen, China

Abstract: Increasing roof albedo (using a "cool" roof) and night ventilation are passive cooling technologies that can reduce the cooling loads in buildings, but the research has not comprehensively explored the potential benefit of integrating these two technologies. This study combines an experiment in the summer and transition seasons with an annual simulation so as to evaluate the thermal performance, energy savings and thermal comfort improvement that could be obtained by coupling a cool roof with night ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…8,98 The first way to apply PDRC is to directly apply a passive PDRC coating on a terrestrial entity that needs to be cooled, such as the cooling roof is shown in Figure 14A. 98,99,[101][102][103][104][105][106][107][108][109] Roofs in most residential buildings are exposed to substantial solar radiation during the daytime, resulting in a high roof temperature (up to 60 C). This heat is transferred to the living space, placing a higher cooling load on the air conditioner.…”
Section: Space Coolingmentioning
confidence: 99%
“…8,98 The first way to apply PDRC is to directly apply a passive PDRC coating on a terrestrial entity that needs to be cooled, such as the cooling roof is shown in Figure 14A. 98,99,[101][102][103][104][105][106][107][108][109] Roofs in most residential buildings are exposed to substantial solar radiation during the daytime, resulting in a high roof temperature (up to 60 C). This heat is transferred to the living space, placing a higher cooling load on the air conditioner.…”
Section: Space Coolingmentioning
confidence: 99%
“…Improvement of building energy efficiency is one of the key issues to achieve energy conservation and environmental sustainability, as buildings contribute over 40% of primary energy consumption and one-third of global CO2 emissions worldwide [1]. One of the effective ways to improve the building performance is to select cool surfaces with high albedo (ability to reflect sunlight, spectrum 0.3 -2.5 μm; also known as solar reflectance) and high thermal emittance (ability to radiate heat, spectrum 4 -80 μm) [2]. Utilizing cool coatings helps save energy [3] and reduce power-plant emissions of CO2, SO2, and NOx in conditioned buildings [4] and improve thermal comfort in non-conditioned buildings [5] in hot weather, while it may also increase heating demand or result in thermal discomfort in cold weather [6].…”
Section: Nomenclaturementioning
confidence: 99%
“…Thus, the annual maintenance costs for non-cool and cool surfaces were set the same. (2) In terms of the initial costs between the cool and non-cool coatings, a guideline released by the U.S. Department of Energy [44] shows that cool surface products are usually similar in cost or slightly more expensive than similar non-cool alternatives. For instance, the median market price of a white single-ply membrane is the same as a black single-ply membrane.…”
Section: Objective Functions and Problems Formulationmentioning
confidence: 99%
“…In China, the building energy demand is huge, which is close to 28% of the energy demand of the whole society [ [1] , [2] , [3] ]. Especially in cold areas, a significant amount of the entire building heat loss is caused by windows [ [4] , [5] , [6] ], and roughly 30% of the entire heat loss occurs through windows and air infiltration [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%